Kv channel gating requires a compatible S4-S5 linker and bottom part of S6, constrained by non-interacting residues - Labro, A; Raes, A; Grottesi, A; Van Hoorick, D; Sansom, M; Snyders, D (Rockefeller University Press, 2008)
Voltage-dependent K⁺ channels transfer the voltage sensor movement into gate opening or closure through an electromechanical coupling. To test functionally whether an interaction between the S4-S5 linker (L45) and the cytoplasmic end of S6 (S6T) constitutes this coupling, the L45 in hKv1.5 was replaced by corresponding hKv2.1 sequence. This exchange was not tolerated but could be rescued by also swapping (S6T). Exchanging both L45 and (S6T) residue substitution scan of L45 and (S6T) in hKv1.5 further shows that (S6T) needs to be α-helical and forms a "crevice" in which residues I422 and T426 of L45 reside. These residues transfer the mechanical energy onto the (S6T) crevice, whereas other residues in (S6T) and L45 that are not involved in the interaction maintain the correct structure of the coupling.